Hofjude ohne Hof. Der Kasseler Oberhofagent Feidel David, ein Vorgänger Mayer Amschel Rothschilds - Battenberg, J. Friedrich (Aschkenas, 2011)
Abstract In her very important monograph »The Court Jew« Selma Stern analysed, 60 years ago, the structural elements of the German Court Jewry in the Baroque Age as a contribution to the History of Absolutism in Europe. The New York exposition with the title »From Court Jews to the Rothschilds – Arts, Patronage, Power«, prepared and procured by Vivian B. Mann and Richard L. Cohen (1996/1997), lately showed different aspects of this development from its beginnings in the $ 17^{th} $ to its end in the early $ 19^{th} $ century. The historical sciences offer less information about the court Jews who were no longer of the classical type (privileged trader and financier of the territorial or imperial courts, such as Samuel Oppenheimer) and not yet of the modern type (independent banker without attachments to the territorial or imperial Courts, such as the early Rothschilds and later on Gerson Bleichröder). The present study is based on newly discovered archival sources about a personality and his family who represent the link between the two types mentioned: Feidel David who, for his part, facilitated the rise of Meyer Amschel Rothschild at the court of the Landgrave of Hesse-Kassel. He anticipated the financial transactions that the Rothschilds continued, completed and extended into a European system.